PENGARUH JUMLAH UANG BEREDAR, NILAI TUKAR, FOREIGN DIRECT INVESTMENT, DAN INDEKS HARGA PERDAGANGAN BESAR TERHADAP EKSPOR INDONESIA TAHUN 2009-2021 - Radifan, Fadhil; Saputra, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of the money supply, exchange rate, foreign direct investment and wholesale trade price index on exports in Indonesia. This study uses a quantitative approach. The method used is Error Correction Model (ECM). The data obtained are secondary data published by the Central Statistics Agency (BPS) in the form of money supply, the wholesale and export price index, the Ministry of Trade in the form of exchange rates and the Investment Coordinating Board (BKPM) in the form of foreign direct investment. The results of this study indicate that the money supply has a positive and significant effect on Indonesian exports in the short and long term. Meanwhile, the exchange rate and foreign direct investment have a negative and significant impact on Indonesia's exports in the short and long term. Also, the wholesale price index has a positive and significant impact on Indonesian exports in the short term.